Institutional Design of Gouramy Cultivation Community Village Panjerejo, Rejotangan, Tulungagung - Samudro*, Bhimo Rizky; Soesilo, Albertus Maqnus; Pratama, Yogi Pasca; Suryantoro, Agustinus; Irawan, BRM Bambang; Prasetyo, Andri; Sistriatmaja, Muhammad Bagus (Universitas Syiah Kuala, 2023)
The existence of an institutional design for consumption fish production is the central aspect of sustainability fishery in Village Panjerejo, Rejotangan, Regency Tulungagung. The position price of fish gourami (consumption fish), which tends to fluctuate and is added to the relative price of artificial feed tall, makes farmer fish consumption must own method alternative in availability feed fish. Fish farmer gouramy expected to be able to organize internal institutions to produce self-sufficient fish feed to reduce production costs. This is a crucial moment. They also have to face a relatively fluctuating revenue/ revenue product tend to decrease. System institutional expected produce pattern independence food, in the sense of ease of price and physical access to meet the needs of farmers of consumption fish.